Dipolar relaxation dynamics at the active site of an ATPase regulated by membrane lateral pressure - Fischermeier, Elisabeth (Angewandte Chemie. International edition, 2017)
The active transport of ions across biological membranes requires their hydration shell to interact with the interior of membrane proteins. However, the influence of the external lipid phase on internal dielectric dynamics is hard to access by experiment. Using the octahelical transmembrane architecture of the copper-transporting P1B-type ATPase from Legionella pneumophila as a model structure, we have established the site-specific labeling of internal cysteines with a polarity-sensitive fluorophore. This enabled dipolar relaxation studies in a solubilized form of the protein and in its lipid-embedded state in nanodiscs. Time-dependent fluorescence shifts revealed the site-specific hydration and dipole mobility around the conserved ion-binding motif. The spatial distribution of both features is shaped significantly and independently of each other by membrane lateral pressure.